2021
DOI: 10.1111/hepr.13602
|View full text |Cite
|
Sign up to set email alerts
|

Potential of ultra‐highly sensitive immunoassays for hepatitis B surface and core‐related antigens in patients with or without development of hepatocellular carcinoma after hepatitis B surface antigen seroclearance

Abstract: Aims Hepatitis B surface antigen (HBsAg) seroclearance indicates a “functional cure” in chronic hepatitis B (CHB) virus infection. However, several cases of hepatocellular carcinoma (HCC) development have been reported after HBsAg seroclearance. We evaluated the potential of HBsAg and hepatitis B core‐related antigen (HBcrAg), measured by the ultra‐highly sensitive assays, in cases with HCC development after HBsAg seroclearance. Methods We enrolled 17 patients with CHB who achieved HBsAg seroclearance, defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…In another study of iTACT-HBcrAg, Suzuki et al reported that the proportion of HBcrAg ≥ 2.7 was significantly higher in the HCC group than the non-HCC group, indicating that the remaining low HBcrAg might predict HCC development, even if HBcrAg seroclearance was achieved according to the conventional assay [90].…”
Section: High-sensitivity Hbcrag Assaymentioning
confidence: 99%
“…In another study of iTACT-HBcrAg, Suzuki et al reported that the proportion of HBcrAg ≥ 2.7 was significantly higher in the HCC group than the non-HCC group, indicating that the remaining low HBcrAg might predict HCC development, even if HBcrAg seroclearance was achieved according to the conventional assay [90].…”
Section: High-sensitivity Hbcrag Assaymentioning
confidence: 99%
“…As another clinical utility, a recent study reported that the prevalence of HBcrAg equal to or greater than 2.7 in the HCC group was significantly higher than that in non‐HCC group (100% [5/5] vs. 33% [4/12], p = 0.029), indicating that residual low HBcrAg might predict HCC development even if HBsAg seroclearance was achieved according to a conventional assay 52 …”
Section: Novel Biomarkers For the Diagnosis Of Hbv Reactivationmentioning
confidence: 99%
“…Collectively, these reports show that serum HBcrAg can predict clinical outcomes, such as HBeAg seroconversion, response to therapy, HBV reactivation, and risk of HCC development [ 100 ].…”
Section: Hbcragmentioning
confidence: 99%